Seasonal variation in quality of grazed forage during a drought year - R.C. Cochran; E.S. Vanzant (Kansas Agricultural Experiment Station Research Reports, 1991)
Concentration of fiber in the forage selected by beef steers grazing bluestem range during a drought year (1989) was highest in the winter but declined substantially in the spring and remained fairly constant throughout summer. Conversely, crude protein concentration was lowest during the winter, peaked during the spring, declined through early summer, but increased in the late summer before declining during the fall. Precipitation was well below normal in all months except August, September, and October, which were above normal. Improvement in forage quality during those months was probably due to stimulation of late-season forage growth in response to elevated precipitation.
Keywords: Cattlemen' s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Range; Forage; Protein; Fiber; Drought